Protocol for a Randomized Hybrid Type 2 Trial on the Implementation of Group Problem Management Plus (PM+) for Venezuelan Women Refugees and Migrants in Colombia - Manaswi Sangraula; M. Claire Greene; Diany Castellar; Jean Carlos Flechas de la Hoz; Jennifer Diaz; Valeria Merino; Lucy Miller-Suchet; Maria Cristobal; Ana Maria Chamorro Coneo; Luisa Morales; Marcela Venegas; Abel Guerrero Gonzalez; et al. (Intervention Journal of Mental Health and Psychosocial Support in Conflict Affected Areas)
Background: Task-sharing interventions have shown to be feasible and effective in reducing symptoms of psychological distress. Research is currently needed on how task-shared interventions can be sustained with less-intensive technical support from mental health providers, often available in controlled research trials. This study protocol aims to evaluate the effectiveness of Group Problem Management Plus (PM+) and the adoption, fidelity and maintenance of the intervention when delivered and supervised by nonspecialists. Methods: This study utilises a type-2 hybrid implementation design to compare participant-level outcomes when the intervention is delivered by nonspecialists who receive technical support by psychologists versus nonspecialised support by lay providers. Venezuelan and Colombian women in Barranquilla, Colombia reporting moderate levels of distress will be randomised (N = 128 total) to receive PM+ delivered by nonspecialists who receive training and supervision by a: 1) psychologist; or 2) nonspecialist. Psychosocial wellbeing, general distress and functioning will be measured at baseline, 1-week and 3-months post intervention. A process evaluation will be guided by the RE-AIM framework. Discussion: Results will determine if Group PM+ is feasible and effective to implement in lower resource contexts with less-intensive specialised support. This research especially has implications for humanitarian settings with a limited number of mental health providers. Trials Registry: ClinicalTrials.gov identifier: NCT05477355